Descriptive Analyses on English Test Items based on the Application of Revised Bloom’s Taxonomy - Imanuel Kamlasi (Metathesis: Journal of English Language, Literature, and Teaching, 2018)
This investigation analyzed the English test items based on the application of revised Bloom’s taxonomy. This study was categorized as descriptive qualitative research. The instrument of this study was English test sheet which was used in final semester test in senior high school. In analyzing the data; the researchers applied four steps: codifying; classifying; analyzing and discussing. Anderson, et.al. (2001) revised the Bloom’s Taxonomy that thinking is an active process so verbs were used rather than nouns. The findings showed that remembering taxonomy made 22 items or 44%. Understanding taxonomy presented 2 items or 4%. Applying taxonomy made 21 items or 42%. Analyzing taxonomy made 5 items or 10%. While there was no item found in both evaluating and creating taxonomy. Therefore; creating taxonomy was not used to ask the students in the English test. Regarding to the findings of this investigation; teachers need to distribute the revised Bloom’s taxonomy in constructing test items. Furthermore; teachers need to use WH questions in the test items.